High-capacity strong-power body-centered cubic structure hydrogen storage alloy and preparation method thereof

Through vacuum suspension smelting and sectional heating and insulation heat treatment methods, a single integrated center cubic structure Ti-Cr-Mo-Ni hydrogen storage alloy was prepared, which solved the problem of insufficient hydrogen release rate of the existing Ti-Cr-Mo base alloy, and realized the High capacity and strong power hydrogen storage effect.

CN119491153APending Publication Date: 2025-02-21YANGTZE DEITA GRADUATE SCHOOI OF BEIJING INST OF TECH (JIAXING) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411752375.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing Ti-Cr-Mo based hydrogen storage alloys have shortcomings in hydrogen release rates, which are difficult to meet application scenarios with high power requirements, such as the transportation field.

Method used

A single-integrated cubic structure Ti-Cr-Mo-Ni hydrogen storage alloy was prepared by vacuum suspension smelting and sectional heating and insulation heat treatment. By adjusting the heating and insulation procedure of heat treatment, the sub-high temperature heterogeneous phases are eliminated and a more uniform alloy structure is obtained.

Benefits of technology

The Ti-Cr-Mo-Ni hydrogen storage alloy with high capacity and strong power has a high hydrogen storage capacity and a fast hydrogen release rate. The time for the alloy to release hydrogen to equilibrium at 313K is ≤70s, and the hydrogen to equilibrium at 353K is ≤70s. The time is ≤30s.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491153A_ABST
    Figure CN119491153A_ABST
Patent Text Reader

Abstract

The invention discloses a high-capacity strong-power body-centered cubic structure Ti-Cr-Mo-Ni hydrogen storage alloy material, the chemical composition general formula of the material is TixCryMozNir, in the formula, x, y, z and r are atomic ratios, and x is more than or equal to 0.35 and less than or equal to 0.4, y is more than or equal to 0.35 and less than or equal to 0.5, z is more than or equal to 0.10 and less than or equal to 0.15, and r is more than or equal to 0.01 and less than or equal to 0.10; the preparation method of the hydrogen storage alloy material mainly comprises the steps of burdening, smelting, heat treatment and gas quenching treatment in sequence. The preparation method is simple, the process is easy to control, the prepared material is stable in structure, uniform in alloy component and uniform in grain size and has excellent reversible hydrogen storage density and hydrogen absorption and desorption power, the reversible hydrogen storage capacity of the material is 2.1 wt.% under 313K, and the time for reaching hydrogen desorption balance is about 1 minute.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state hydrogen storage, and relates to a high-capacity, high-power body-centered cubic structure hydrogen storage alloy and a preparation method thereof. The alloy can be used as a hydrogen storage material for vehicle-mounted hydrogen storage tanks and a key hydrogen storage material for hydrogen storage systems for ships. Background Art

[0002] As the global demand for clean energy grows day by day, the development of new clean energy has become an important direction for responding to climate change and achieving energy transformation. Among them, hydrogen energy has a wide range of sources. Hydrogen can be produced by water electrolysis, fossil fuel reforming or biomass conversion. Its fuel has high calorific value, zero pollution during combustion, and large-scale and long-term energy storage characteristics. It is an effective way to alleviate environmental crises such as global warming. At the same time, many countries and regions around the world are increasing investment in the hydrogen energy industry. The hydrogen energy industry chain is being continuously constructed and improved. Hydrogen energy has initially achieved demonstration applications in the fields of hydrogen energy transportation and hydrogen energy storage.

[0003] The hydrogen energy industry mainly covers three key parts: hydrogen production, hydrogen storage and transportation, and hydrogen application. Among them, hydrogen storage and transportation is an important link connecting upstream and downstream industries. At this stage, high-pressure hydrogen storage is a more common hydrogen storage and transportation technology. However, high-pressure hydrogen storage has shortcomings such as relatively low hydrogen storage density and greater safety risks. Especially in the development process of hydrogen energy towards large-scale application, these problems have become more and more obvious, forming an obstacle to the efficient advancement of the hydrogen energy industry. Therefore, it is urgent to develop new, safe and efficient hydrogen storage and transportation technologies. Solid-state hydrogen storage technology based on hydrogen storage alloys has the highest volumetric hydrogen storage density and safety performance among current hydrogen storage technologies, and has the potential for large-scale promotion and application. The classic solid-state hydrogen storage alloy system is mainly divided into AB 2 , AB 5 And V-based solid solution alloy. AB 2 AB type hydrogen storage alloy absorbs and releases hydrogen quickly and has low cost, but the hydrogen storage capacity is relatively low (about 1.8wt.%); 5The alloy has a high cycle life and is easy to activate, but the cost is high and the hydrogen storage capacity is low (about 1.5wt.%); the V-based BCC body-centered cubic solid solution hydrogen storage alloy has a high hydrogen storage capacity (about 4.0wt.%), good power performance, and a high cycle life, but the cost is extremely high due to the high price of metal vanadium. The octahedral and tetrahedral lattice gaps of the body-centered cubic structure of hydrogen storage alloy materials can be used as hydrogen storage sites, and it is the crystal structure with the highest theoretical hydrogen storage capacity. Therefore, alloys based on non-precious metal systems with a body-centered cubic structure have great development potential. Based on this, Hu et al. reported Ti-Cr-Mo-based hydrogen storage materials, which have high hydrogen storage capacity and low raw material cost, and are one of the most promising hydrogen storage materials. However, the current hydrogen desorption rate of Ti-Cr-Mo alloys is slow, and its hydrogen desorption kinetics are difficult to meet the needs of application scenarios with high power requirements, such as the transportation field. Common methods for modifying hydrogen storage alloys include alloying, nano-sizing, and catalyst addition. Among them, alloying is the most effective method to improve hydrogen storage alloys. Adding elements with hydrogen decomposition catalysis to alloying can specifically improve the hydrogen decomposition rate of Ti-Cr-Mo matrix alloy materials. However, the introduction of other elements into Ti-Cr-Mo based hydrogen storage materials will change the thermal stability of the body-centered cubic structure. In quaternary and above multi-element alloy systems, the conditions for the formation of a single-phase structure are extremely harsh, and the temperature and component ranges for stable existence are very small. It is necessary to strictly control the process conditions to obtain a single-phase body-centered cubic structure of quaternary and above multi-element alloys. Many studies have shown that the Ni element has a significant effect on improving the hydrogen decomposition kinetics of hydrogen storage alloys. The Ni element itself has hydrogen decomposition catalytic activity, and it belongs to the B-side hydrogen decomposition element. The addition of the Ni element will reduce the stability of the hydride. However, it is difficult to prepare a Ti-Cr-Mo-Ni quaternary single-phase body-centered cubic structure alloy using existing technology. There is no relevant report on the Ti-Cr-Mo-Ni system body-centered cubic structure hydrogen storage alloy. Summary of the invention

[0004] The purpose of the present invention is to provide a high-capacity and high-power body-centered cubic Ti-Cr-Mo-Ni hydrogen storage alloy material and a preparation method thereof. The present invention mainly adopts a vacuum suspension melting and a step-by-step heating and insulation heat treatment method to prepare a single body-centered cubic Ti-Cr-Mo-Ni hydrogen storage alloy by adjusting the heating and insulation program of the heat treatment. The specific technical scheme is as follows:

[0005] The method of the present invention comprises the following specific steps:

[0006] (1) the ingredients are prepared according to the element ratio of the general formula of the hydrogen storage alloy composition, and then vacuum suspension melting is performed. Considering the volatilization loss during melting, the volatilization amount of the corresponding elements is supplemented and increased during the ingredients preparation. Then, a conventional vacuum suspension melting method is used to prepare a cast alloy, the melting vacuum degree is -0.02MPa, the inert gas used is high-purity argon, the melting current is 30-70A, the melting time is 300-500s / time, and the melting number is 4 times to obtain a cast alloy;

[0007] (2) placing the as-cast alloy of step (1) in a quartz tube with a diameter of 3 cm, evacuating the quartz tube, introducing high-purity argon gas, and then sealing the quartz tube. Then, placing the quartz tube containing the alloy in a quartz tube with a diameter of 4.5 cm again, evacuating the quartz tube, introducing high-purity argon gas, and then sealing the tube for the second time;

[0008] (3) placing the quartz tube containing the alloy in step (2) in a heat treatment furnace for heat treatment, wherein the heat treatment procedure is as follows:

[0009] The first heating stage: from room temperature to 600°C, the heating rate is 10°C / min;

[0010] The second heating stage: from 600℃ to 1200℃, the heating rate is 5℃ / min, and the temperature is kept for 30min;

[0011] The third heating stage: from 1200°C to 1400°C, the heating rate is 1°C / min, and the temperature is kept at this temperature for 20 minutes.

[0012] Cooling stage: After the alloy insulation time is over, gas quenching cooling treatment is immediately carried out. The gas pressure of the gas quenching treatment is 15 bar, the flow rate is 10 m / s, and the ventilation time is 20 min.

[0013] Due to the adoption of the above technical solution, the present invention has the following beneficial effects compared with the prior art:

[0014] 1. The hydrogen storage alloy of the present invention is prepared by a staged heating and heat preservation heat treatment method, which is helpful to eliminate the sub-high temperature impurity phase, so that the prepared body-centered cubic structure is single and the alloy structure is more uniform.

[0015] 2. The hydrogen storage alloy of the present invention is prepared by gas quenching, which has a faster cooling rate, more convenient operation, lower cost and is suitable for large-scale industrial application compared to water quenching.

[0016] 3. The high-capacity and high-power body-centered cubic structure Ti-Cr-Mo-Ni hydrogen storage alloy prepared by the present invention has a high hydrogen storage capacity, and the reversible mass hydrogen storage density of the alloy is ≥2.1wt.%; it has a fast hydrogen desorption rate, and the time for the alloy to desorb hydrogen to equilibrium at 313K is ≤70s, and the time for desorbing hydrogen to equilibrium at 353K is ≤30s.

[0017] 4. The high-capacity and high-power single body-centered cubic structure Ti-Cr-Mo-Ni hydrogen storage alloy prepared by the present invention has a stable structure, outstanding performance, broad application prospects, and certain promotion and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Ti prepared in Example 1 of the present invention 0.40 Cr 0.48 Mo 0.10 Ni 0.02 and Ti prepared in Example 2 0.38 Cr 0.45 Mo 0.12 Ni 0.05 X-ray diffraction pattern (XRD) of hydrogen storage alloy;

[0019] Figure 2 Ti prepared in Example 1 of the present invention 0.40 Cr 0.48 Mo 0.10 Ni 0.02 and Ti prepared in Example 2 0.38 Cr 0.45 Mo 0.12 Ni 0.05 Hydrogen storage alloy dehydrogenation rate curve;

[0020] Figure 3 Ti prepared in Example 1 of the present invention 0.40 Cr 0.48 Mo 0.10 Ni 0.02 and Ti prepared in Example 2 0.38 Cr 0.45 Mo 0.12 Ni 0.05 pct curve of hydrogen storage alloy. DETAILED DESCRIPTION

[0021] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0022] Example 1Ti 0.40 Cr 0.48 Mo 0.10 Ni 0.02 Preparation method of hydrogen storage alloy

[0023] According to the composition Ti 0.40 Cr 0.48 Mo 0.10 Ni 0.02 The material is prepared, and the metal element is filled according to the melting point during the smelting process. The smelting is carried out according to the conventional vacuum suspension smelting steps, the smelting current is 40-60A, the smelting time is 400s / time, and the number of smelting is 4 times; the cast alloy is placed in a quartz tube with a diameter of 3 cm, and then the quartz tube is evacuated, and high-purity argon is introduced, and then the quartz tube is sealed, and then the quartz tube containing the alloy is placed in a quartz tube with a diameter of 4.5 cm again, the quartz tube is evacuated, and high-purity argon is introduced, and then the tube is sealed for the second time, and then the quartz tube is sealed and heat treated, when the temperature is heated from room temperature to 600°C, the heating rate is 10°C / min; then the temperature is continued to rise to 1200°C at a heating rate of 5°C / min, and the temperature is kept for 30 minutes; then the temperature is continued to rise to 1400°C at a heating rate of 1°C / min, and the temperature is kept for 20 minutes; after reaching the insulation time, gas quenching treatment is carried out. The samples obtained above were cut into 3 mm cubes and the hydrogen storage properties of the alloys were measured using Sievert's method.

[0024] like Figure 1 As shown, the alloy prepared in Example 1 is a body-centered cubic single-phase structure.

[0025] like Figure 2 As shown, the alloy prepared in Example 1 reaches hydrogen desorption equilibrium in 58 s at 313 K and in 20 s at 353 K.

[0026] like Figure 3 As shown, the maximum hydrogen storage capacity of the alloy prepared in Example 1 is 3.07wt.%, and the maximum reversible hydrogen release amount is 2.02wt.%.

[0027] Example 2Ti 0.38 Cr 0.45 Mo 0.12 Ni 0.05 Preparation method of hydrogen storage alloy

[0028] According to the composition Ti 0.38 Cr 0.45 Mo 0.12 Ni 0.05The material is prepared, and the metal element is filled according to the melting point during the smelting process. The smelting is carried out according to the conventional vacuum suspension smelting steps, the smelting current is 40-65A, the smelting time is 450s / time, and the number of smelting is 4 times; the cast alloy is placed in a quartz tube with a diameter of 3 cm, and then the quartz tube is evacuated, and high-purity argon is introduced, and then the quartz tube is sealed, and then the quartz tube containing the alloy is placed in a quartz tube with a diameter of 4.5 cm again, the quartz tube is evacuated, and high-purity argon is introduced, and then the tube is sealed for the second time, and then the quartz tube is sealed and heat treated, when the temperature is heated from room temperature to 600°C, the heating rate is 10°C / min; then the temperature is continued to rise to 1200°C at a heating rate of 5°C / min, and the temperature is kept for 30 minutes; then the temperature is continued to rise to 1400°C at a heating rate of 1°C / min, and the temperature is kept for 20 minutes; after reaching the insulation time, gas quenching treatment is carried out. The samples obtained above were cut into 3 mm cubes and the hydrogen storage properties of the alloys were measured using Sievert's method.

[0029] like Figure 1 As shown, the alloy prepared in Example 2 has a body-centered cubic single-phase structure.

[0030] like Figure 2 As shown, the alloy prepared in Example 2 reaches hydrogen desorption equilibrium in 59 s at 313 K and in 21 s at 353 K.

[0031] like Figure 3 As shown, the maximum hydrogen storage capacity of the alloy prepared in Example 2 is 2.97wt.%, and the maximum reversible hydrogen release amount is 2.11wt.%.

[0032] Example 3Ti 0.40 Cr 0.40 Mo 0.10 Ni 0.10 Preparation method of high entropy alloy

[0033] According to the composition Ti 0.40 Cr 0.40 Mo 0.10 Ni 0.10The material is prepared, and the metal element is filled according to the melting point during the smelting process. The smelting is carried out according to the conventional vacuum suspension smelting steps, the smelting current is 40-70A, the smelting time is 600s / time, and the number of smelting is 4 times; the cast alloy is placed in a quartz tube with a diameter of 3 cm, and then the quartz tube is evacuated, and high-purity argon is introduced, and then the quartz tube is sealed, and then the quartz tube containing the alloy is placed in a quartz tube with a diameter of 4.5 cm again, the quartz tube is evacuated, and high-purity argon is introduced, and then the tube is sealed for the second time, and then the quartz tube is sealed and heat treated, when the temperature is heated from room temperature to 600°C, the heating rate is 10°C / min; then the temperature is continued to rise to 1200°C at a heating rate of 5°C / min, and the temperature is kept for 30 minutes; then the temperature is continued to rise to 1400°C at a heating rate of 1°C / min, and the temperature is kept for 20 minutes; after reaching the insulation time, gas quenching treatment is carried out. The samples obtained above were cut into 3 mm cubes and the hydrogen storage properties of the alloys were measured using Sievert's method.

[0034] The test results show that the alloy prepared in Example 3 is a body-centered cubic single-phase structure, the maximum hydrogen storage capacity of the alloy is 3.13wt.%, the reversible hydrogen desorption is 2.0wt.%, the alloy reaches hydrogen desorption equilibrium in 53s at 313K, and reaches hydrogen desorption equilibrium in 18s at 353K.

[0035] Comparative Example 1

[0036] In this comparative example, a high entropy alloy with the same chemical formula as in Example 1 was prepared, and two groups of samples, A and B, were prepared respectively. The chemical formula of the alloy was the same as in Example 1, and the preparation method was similar to that in Example 1, except that the heat treatment process during the preparation was different, as described below.

[0037] Group A: The alloy samples were heated directly from room temperature to 1400°C at a rate of 5°C / min and kept at this temperature for 20 min.

[0038] Group B: The alloy samples were heated from room temperature to 1400°C at a heating rate of 1°C / min and kept at this temperature for 20 min.

[0039] The products prepared from Group A and Group B of Comparative Example 1 were subjected to a series of performance tests, and the specific results are as follows.

[0040] The test results show that

[0041] The alloy prepared in Group A of Comparative Example 1 is not a body-centered cubic single-phase structure, and further contains 15% C14-type laves segregation phase; the maximum mass hydrogen storage density of the alloy is 2.47wt.%.

[0042] The alloy prepared in Group B of Comparative Example 1 is not a body-centered cubic single-phase structure, and further contains 20% C14-type laves segregation phase; the maximum mass hydrogen storage density of the alloy is 2.01wt.%.

[0043] Comparative Example 2

[0044] In this comparative example, a high entropy alloy having the same general chemical formula as that of Example 1 is prepared. The chemical formula of the alloy is the same as that of Example 1, and the preparation method is similar to that of Example 1. The only difference is that the cooling method after heat treatment is different, as follows.

[0045] The alloy sample was heated from room temperature to 600°C at a rate of 10°C / min, then to 1200°C at a rate of 5°C / min, and then to 1400°C at a rate of 1°C / min, and kept at this temperature for 20 min.

[0046] After the heat preservation is completed, the alloy sample is cooled naturally in the furnace to obtain a hydrogen storage alloy.

[0047] The product prepared in Comparative Example 2 was subjected to a series of performance tests, and the specific results are as follows.

[0048] The test results show that

[0049] The alloy prepared in Comparative Example 2 is not a body-centered cubic single-phase structure, and further contains 19% C14-type laves segregation phase; the maximum mass hydrogen storage density of the alloy is 2.33wt.%.

[0050] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.

Claims

1. A high-capacity and high-power body-centered cubic structure Ti-Cr-Mo-Ni hydrogen storage alloy material, characterized by: Its chemical composition is Ti x Cr y Mo z Ni r , where x, y, z, r are atomic ratios, and 0.35≤x≤0.4, 0.35≤y≤0.5, 0.10≤z≤0.15, 0.01≤r≤0.

10.

2. The high capacity and high power body-centered cubic structure Ti-Cr-Mo-Ni hydrogen storage alloy material according to claim 1 is characterized in that: The reversible mass hydrogen storage density of the alloy is ≥2.1wt.%, the time for the alloy to release hydrogen to equilibrium at 313K is ≤70s, and the time for the alloy to release hydrogen to equilibrium at 353K is ≤30s.

3. The method for preparing the high-capacity and high-power body-centered cubic Ti-Cr-Mo-Ni hydrogen storage alloy material according to claim 1 or 2, characterized in that The steps include: (1) Melting The ingredients are prepared according to the ratio of elements in the general formula of the hydrogen storage alloy composition, and then vacuum suspension melting is performed, and the volatilization amount of the corresponding elements is supplemented and increased during the preparation; the cast alloy is prepared by a conventional vacuum suspension melting method; (2) Sealing the tube The cast alloy obtained in step (1) is placed in a quartz tube with a diameter of 3 cm, and then the quartz tube is evacuated and high-purity argon gas is introduced, and then the quartz tube is sealed, and then the quartz tube containing the alloy is placed again in a quartz tube with a diameter of 4.5 cm, and the quartz tube is evacuated and high-purity argon gas is introduced, and then the tube is sealed for the second time; (3) Heat treatment The quartz tube containing the alloy obtained in step (2) is placed in a heat treatment furnace for heat treatment, and the heat treatment procedure is as follows: The first heating stage: from room temperature to 600°C, the heating rate is 10°C / min; The second heating stage: from 600℃ to 1200℃, the heating rate is 5℃ / min, and the temperature is kept for 30min; The third heating stage: from 1200°C to 1400°C, the heating rate is 1°C / min, and the temperature is kept at this temperature for 20 minutes. Cooling stage: After the alloy insulation time is over, gas quenching cooling treatment is immediately carried out. The gas pressure of the gas quenching treatment is 15 bar, the flow rate is 10 m / s, and the ventilation time is 20 min.

4. The method for preparing the high-capacity and high-power body-centered cubic Ti-Cr-Mo-Ni hydrogen storage alloy material according to claim 3, characterized in that: In step (1), the melting vacuum is -0.02MPa, the inert gas used is high-purity argon, the melting current is 30-70A, the melting time is 300-500s / time, the melting number is 4 times, and a cast alloy is obtained.